Febrile Infection-Related Epilepsy Syndrome without Detectable Autoantibodies and Response to Immunotherapy: A Case Series and Discussion of Epileptogenesis in FIRES - van Baalen, Andreas; Häusler, Martin; Plecko-Startinig, Barbara; Strautmanis, Jurgis; Vlaho, Stefan; Gebhardt, Boris; Rohr, Axel; Abicht, Angela; Kluger, Gerhard; Stephani, Ulrich; Probst, Christian; Vincent, Angela; Bien, Christian G. (Neuropediatrics, 2012)
Febrile infection-related epilepsy syndrome (FIRES) is a severe postinfectious epileptic encephalopathy in previously healthy children and has three phases: the initial phase with a simple febrile infection, a few days later the acute phase characterized by a peracute onset of highly recurrent seizures or refractory status epilepticus often with no more fever and generally without additional neurological features (the classical pure seizure phenotype), and last, the chronic phase with a drug-resistant epilepsy and neuropsychological impairments. FIRES seems to be sporadic and very rare: we estimated the annual incidence in children and adolescents by a prospective hospital-based German-wide surveillance as 1 in 1,000,000. Because of the preceding infection and lacking evidence of infectious encephalitis, an immune-mediated pathomechanism and, therefore, a response to immunotherapies may be involved. To test the hypothesis that antibodies against neuronal structures cause FIRES, we analyzed sera of 12 patients aged 2 to 12 years (median 6 years) and cerebral spinal fluids (CSFs) of 3 of these 12 patients with acute or chronic FIRES. We studied six patients (two including CSF) 1 to 14 weeks (median 3 weeks) and six patients 1 to 6 years (median 3.5 years) after seizure onset. All samples were analyzed for antibodies against glutamate receptors of type N-methyl-D-aspartate (NMDA) and type α-amino-3-hydroxy-5-methyl-4-isoxazoleproprionic acid (AMPA), gamma-aminobutyric acid (GABA)B-receptors, voltage-gated potassium channel (VGKC)-associated proteins leucin-rich glioma inactivated 1 (LGI1) and contactin-associated protein like 2 (CASPR2), and glutamic acid decarboxylase (GAD) by a multiparametric recombinant immunofluorescence assay employing human embryonic kidney (HEK) cells transfected with cDNAs for the antigens. In addition, indirect immunohistochemistry using rat whole-brain sections was done in three patients. Finally, sera of 10 patients were tested for VGKC complex antibodies by radioimmunoprecipitation assay (RIA). None of the antibody tests were positive in any of the patients. Moreover, steroids, immunoglobulins, and plasmapheresis had no clear effect in the seven patients receiving immunotherapy. The failure of antibody-detection against the known neuronal antigens as well as the ineffectiveness of immunotherapy questions a role for autoantibodies in the epileptogenesis of classical FIRES. As we discuss, other underlying causes need to be considered including the possibility of a mitochondrial encephalopathy.
Keywords: antibody; epilepsy; fires; immunotherapy; infection; inflammation; status epilepticus